1981
DOI: 10.1007/bf01353060
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the external validity of a social simulation measure of social skills

Abstract: Two studies were conducted in order to obtain evidence regarding the external validity of a social simulation measure of social skills. The first study employed a contrasted group design, with the groups consisting of National Guardsmen and psychiatric patients. As predicted, trained judges rated the performances of the National Guardsmen in the simulations as more skillful and appearing less anxious than the psychiatric patients. In the second study, trained judges" ratings of psychiatric patients" performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…Additionally, SSIT performance of schizophrenics was rated as more anxious and less skillful than either of the other groups, and nonschizophrenics were rated as less skillful than comparison subjects. These findings were consistent with those of Wessberg et al (1981) and suggest that patients exhibit deficiencies in the sending stage of social skill, as well as in the receiving and processing stages (Wallace et al, 1980).…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, SSIT performance of schizophrenics was rated as more anxious and less skillful than either of the other groups, and nonschizophrenics were rated as less skillful than comparison subjects. These findings were consistent with those of Wessberg et al (1981) and suggest that patients exhibit deficiencies in the sending stage of social skill, as well as in the receiving and processing stages (Wallace et al, 1980).…”
Section: Discussionsupporting
confidence: 85%
“…The subjects’ self-ratings score on an informational test, global ratings by the experimenter and by the partners, and quantitative and qualitative ratings of specific behaviors as seen on videotape all produced highly consistent appraisals of the social skill level of the subjects. Wessberg et al (1981) have also shown with quite different populations that ratings of social skills from a variety of sources, including self-ratings, can show a high level of agreement.…”
Section: Discussionmentioning
confidence: 92%
“…A number of studies have demonstrated a correspondence between behavior seen on role-play tests and that seen in naturalistic analogs (Blumer & McNamara, 1982; Merluzzi & Biever, 1987; Wessberg, Mariotto, Conger, Conger, & Farrell, 1979), whereas others have found only a modest relationship between behavior on standard role-play procedures and in matched criterion situations (Bellack, Hersen, & Lamparski, 1979; Higgins, Alonso, & Pendleton, 1979; Kern, Miller, & Eggers, 1983). The few studies conducted with psychiatric patients have also yielded inconsistent results (Bellack, Hersen, & Turner, 1978; Helzel & Rice, 1985; Wessberg et al, 1981). For the most part, role-play tests appear to account for a moderate proportion of variance in ratings derived from naturalistic test criteria, with molar measures (e.g., overall social skill) accounting for more variance than molecular-response components (e.g., eye contact and speech disruptions).…”
mentioning
confidence: 99%